Makna Penderitaan dalam Masyarakat Jawa - Yohanes Heri Widodo (Jurnal Orientasi Baru, 2008)
Suffering is a human experience that touches the depth of its being. At on point suffering is present as terror against human life. Suddenly it came unpredictably. Going through an experience of terror or facing this possibility, a question was raised: why do people have to suffer such terror? Is there any possible meaning in it? Within a Javanese society, a search for meaning of a human phenomena of suffering is closely related to the origin and the goal of human life. Somehow, an experience of suffering has an edifying and positive aspect for each individual as well as human communities in general. It poses a question to be answered for the betterment of human relations and their presence in the universe.